Nanostructured Photoelectrochemical Biosensing Platform for Cancer Biomarker Detection. (2017) - Voccia, Diego; Bettazzi, Francesca; Laschi, Serena; Gellini, Cristina; Pietraperzia, Giangaetano; Falciola, Luigi; Pifferi, Valentina; Ingrosso, Chiara; Placido, Tiziana; Comparelli, Roberto; Curri, M. Lucia; Palchetti, Ilaria
Abstract: The innovative photoelectrochemical properties of multifunctional nanomaterials are here investigated for the development of biosensing platforms for rapid and sensitive detection of a class of cancer biomarker candidates, known as microRNAs. Many different transducers have been proposed, so far, for microRNA detection. Recently, with the emergence of novel photoelectrochemically active species and new detection schemes, photoelectrochemistry has received increasing attention. Gold nanostructures have been, here, used to modify TiO2 electrodes. The surface of the nanostructured platform has been modified by nucleic acid capture probes (CPs). Biotinylated target miRNAs have been recognized by the specific CPs. The biosensing platform has been incubated with streptavidin alkaline phosphatase and exposed to a proper substrate. The product of the enzymatic reaction has been photoelectrochemically monitored. A compact and hand-held analytical device has been developed in order to have a final prototype in line with the concept of point of care testing.